Canadian Mining and Labour Struggles in Mexico: The Challenges of Union Organizing and the Weaknesses of Corporate Social Responsibility - Bocking, Paul G. (McMaster University, 2012)
Focusing on a case study of a union organizing effort at the La Platosa mine in northern Mexico from 2009-2012, this paper studies the challenges facing labour activism at Canadian mining companies in Mexico within the context of the North American Free Trade Agreement. The positions of the Mexican and the Canadian governments in relation to contemporary workers’ struggles in Mexico’s mining sector are considered, particularly the latter’s adoption of a ‘corporate social responsibility’ approach to addressing the activities of Canadian extractive firms abroad. By studying the outcome of the request for mediation filed by La Platosa miners with the Canadian government’s Extractive Sector CSR office in 2011 and evaluating the evolution of this government’s policy approach to extractive companies abroad since 2009, we find that CSR as practiced by the Canadian government has been ineffective at mitigating abusive practices by Canadian mining companies in Mexico and that an alternate outcome is not to be expected under existing policy structures. The relative strengths and weaknesses exhibited during labour organizing at the La Platosa mine are evaluated to find both locally specific and more broadly applicable strategies which could be applied to union renewal, both by workers employed under NAFTA’s transnational sector, and by the general labour movement.

A Loyalist Plantation in Nova Scotia, 1784-1800 - Cottreau-Robins, Catherine M. A. (Dalhousie University, 2012)
At the close of the American Revolution thousands of American Loyalists were forced into exile and made their way to British colonies beyond the United States. Most of the Loyalists landed in British North America, particularly the Maritimes. Along with the trauma and losses of the conflict, the Loyalists brought with them a way of doing things, an intense political history, and ideas concerning the imperial structure that framed their everyday lives. This dissertation is a study of the Loyalists. Specifically, it explores a prominent Loyalist and his journey from Massachusetts to Nova Scotia along with family members, servants, and labourers, including enslaved persons. A central objective of the dissertation is to illuminate the story of the enslaved and magnify their place in Nova Scotia’s eighteenth century colonial history narrative. The objective is addressed by adapting a holistic perspective that considers a single geography – the plantation. The holistic perspective, developed through an interdisciplinary methodology, explores the people, places and culture that formed the Loyalist plantation and were informed by it. The picture that emerges is one that puts into place the structure and organization of a Loyalist plantation in the late eighteenth century. This dissertation argues that an interdisciplinary approach is fundamental when exploring the subject of the plantation and its inhabitants in Nova Scotia. Through study of the slaveholder and the comparison of his plantation spaces, the dissertation argues for Loyalist continuity. Such continuity confirmed a slaveholding culture during the mass migration. Finally, this dissertation argues that the Loyalist period can be described as Nova Scotia’s Age of Slavery. The Loyalist migration represents an unprecedented arrival of enslaved persons to the province. Furthermore, the Loyalist migration represents the unprecedented arrival of a political and ideological framework that carried within it perceptions of race and seeds of discrimination that took root.

Neoliberalising Immigration in Canada: The Pilot Project for Occupations Requiring Lower-Levels of Formal Training and the Expansion of Canada's Temporary Foreign Worker Program - Cragg, C. Andrew (Trent University, 2012)
There has been a significant expansion in Canada's Temporary Foreign Worker Program (TFWP) over the past ten years. The Pilot Project for Occupations Requiring Lower Levels of Formal Training (PPORLLFT), a sub program of the TFWP, has been leading this expansion. Drawing upon testimony given to the Parliamentary Standing Committee on Citizenship and Immigration, this thesis examines the development and expansion of the program, since its inception in 2002, and shows that it is connected to the ongoing process of neoliberalisation in Canada. One significant example of this connection is the program's support for increases in two-step immigration streams that involve employer sponsorship for successful transition to permanent residency; this increase represents a privatisation of citizenship decisions. More than this, the neoliberal aspects of the PPORLLFT have increased inequality and the ability of employers to have a more disciplined workforce. This has decreased the ability of working people to have influence in their workplace and over economic policy more generally.
Keywords: Immigration; Neoliberalism; Temporary Foreign Workers

Labour and Literature in the 'West Beyond the West' - Diotte, Mark Vincent (University of British Columbia, 2012)
The literature of British Columbia and the study of labour therein have been largely ignored in academic criticism. I address this deficiency by foregrounding labour in the prose literature of British Columbia as well as the significance of British Columbia literature itself. My introductory literature review demarcates the field, situates the authors and texts I take up, and points to the general importance of such a study. Chapter two begins by analyzing the male-dominant labour narrative in Bertrand Sinclair’s The Inverted Pyramid and Roderick Haig-Brown’s On the Highest Hill and Timber—each focused on the theme of logging. Rather than an overarching argument, the section on Sinclair addresses many concepts, including Pierre Bourdieu’s theory of fields, a connection between environmental conservationism and loggers, and a cooperative economic model that opposes capitalism. Likewise, in Haig-Brown I focus on his treatment of danger in the logging industry, the oft-forgotten history of Canada’s national parks, the way that language connects people to nature, and the presence of homosocial and homosexual relationships in logging. My project shifts in chapter three from logging to orcharding and from novels to three works of creative non-fiction by Harold Rhenisch:Out of the Interior: The Lost Country, Tom Thomson’s Shack, and The Wolves at Evelyn: Journeys through a Dark Century. Operating out of a site of tension and contradiction,Rhenisch resists what he sees as the dominant discourses in the Interior of British Columbia. In my fourth chapter I return to novels but move from a study of manual labour to white collar labour. Here the phrase “white collar” becomes an analytical lens to view labour stratification, exploitation, authorship, sexism, and agency in Douglas Coupland’s JPod, Robert Harlow’s Scann, and Jen Sookfong Lee’s the end of east. In chapter five, I conclude by using Daphne Marlatt’s novel Ana Historic as a way to reflect on the positions of chapters two through four. Marlatt’s criticism of male dominant conceptions of history and patriarchal systems of power illuminates the texts I have taken up and reveals possibilities for further analysis, debate, and discussion.

The Class Idea: Politics, Ideology, and Class Formation in the United States and Canada in the Twentieth Century - Eidlin, Barry (University of California, Berkeley, 2012)
Why are class politics more prevalent in Canada than in the U.S., even though the two countries share similar cultures, societies, and economies? Many view this crossborder distinction as a byproduct of longstanding differences in political cultures and institutions, but I find that it is actually a relatively recent divergence resulting from how the working class was politically incorporated in both countries before, during, and after World War II. My central argument is that in Canada, this incorporation process embedded "the class idea"--the idea of class as a salient, legitimate political category--more deeply in policies, institutions, and practices than in the U.S.Out of the social and political struggles of that period emerged two working class movements that, although bearing a surface resemblance, were organized along different logics. In Canada, the working class was incorporated as a class representative, whereas in the U.S. It was incorporated as an interest group. That difference in political incorporation enabled or constrained labor's legitimacy and organizational capacity in different ways in both countries. Canadian labor's role as a class representative legitimized it and expanded its organizational capacity, while U.S. labor's role as an interest group delegitimized it and undermined its organizational capacity.I show this through a detailed analysis of trajectories of labor movement strength in both countries over the course of the twentieth century, as measured by unionization rates, or union density. Starting from the observation that union density was very similar in both countries until the mid-1960s, then diverged, I first examine competing explanations for this divergence. Having illustrated their strengths and limitations, I then develop an argument showing how the divergence in working class organizational strength was the outcome of struggles for political incorporation.I identify two key moments that shaped these different processes of political incorporation. The first was the restructuring of party-class alliances in both countries in the 1930s and 40s, where U.S. labor decisively abandoned the project of building an independent working class party in favor of an alliance with the Democratic Party, at the same moment that Canadian labor forged an independent class alliance with progressive agrarian forces under the banner of the CCF. The second was differences in the effects of postwar Red scares on the relationship between labor and the left in both countries. While anti-Communism took its toll on working class movements in both countries, the labor-left alliance was severed in the U.S., but only strained in Canada. The outcome of these processes was a U.S. labor movement that conceived of itself more as an interest group representing a specific constituency within the Democratic Party, and a Canadian labor movement that conceived of itself more as a class representative with closer ties to a broader social movement.Differences in labor's political incorporation also shaped the formation and development of the regimes governing labor-management relations in both countries. The Canadian labor regime was created as a result of working class upsurge from below, whereas the U.S. labor regime was created as part of an elite reform project from above. This original difference influenced the organizing logics of each regime. Whereas the Canadian labor regime was organized around recognizing the existence of class conflict and seeking to mitigate it, the U.S. regime was organized around protecting workers' individual rights. Although this created a more interventionist Canadian system that restricted labor's scope of action in important ways, it also reinforced a collective, oppositional class identity vis-à-vis both employers and the state. Meanwhile, the U.S. system's focus on rights led to a stronger focus on legalistic proceduralism and imposing a formal equality between labor and management that obscured the power imbalance inherent in the employment relationship. Additionally, labor drew different lessons from these different processes of regime formation. Whereas Canadian labor learned the value of winning gains through disruptive mass mobilization, U.S. labor learned the value of winning gains through sympathetic politicians and favorable legal precedents.The combination of a more protective and institutionally stable labor regime and a labor movement more accustomed to winning gains through mass mobilization, Canadian labor was better positioned to defend itself than its U.S. counterpart when employers began a counter-offensive beginning in the late 1960s. While U.S. labor spiraled into decline, Canadian labor proved more resilient, leading to the divergence in union density rates.

Permanent Worker, Temporary Resident: Media Representations of Canada's Live-in Caregiver Program - Gilliland, Julia Sarah Jane (University of Victoria, 2012)
The Live-in Caregiver Program is a temporary foreign worker program that allows workers to come to Canada in order to labour as private caregivers for children, the elderly, and disabled individuals. This program allows caregivers to apply for permanent residency after the successful completion of 24 months of full time work. There are a number of scholars, advocacy groups, former caregivers, and other parties that have raised concerns about certain regulations of this program. For example, caregivers under this program have an employer-specific work permit, must live in the homes of the employers, and have no external monitoring of their work environments. Subsequently, the Live-in Caregiver Program has been seen as problematic because of the high number of abusive labour situations. This thesis is dedicated to an analysis of how the Canadian news print media represents the Live-in Caregiver Program. Although there has been much research done on migrant care work within Canada, and around the world, there are few studies on how the news media construct arguments that describe these transnational labour flows. The main topics that guided the research questions for this thesis were: temporary foreign worker programs; citizenship status; globalized, gendered, and racial stereotypes; the live-in regulation; employer specific work permits, and power relations in the labour relationship. This research was not geared to proving or disproving the main findings of key migrant domestic worker literature, rather it was focused on how these conclusions are interpreted, transferred and argued within a publically accessible format, Canadian news print media. This analysis revealed how journalists within Canadian news media construct important cultural narratives to persuade audiences to either reject the LCP as exploitative and problematic, or embrace it as economically beneficial.
Keywords: Social sciences

Harvesting Power and Subjugation: Canada's Seasonal Agricultural Workers Program in Historical Context - Glassco, Clare (Trent University, 2012)
This thesis explores the Canadian state's rationale for the creation and perpetuation of the Seasonal Agricultural Worker's Program (SAWP). Informed by and building on the writing of Canadian political economists, this thesis provides a composite history of the program from its creation in 1966 to its current-day incarnation. While many scholars have looked to neo-liberalism to analyze the program, SAWP existed long before the term entered the political lexicon and instead fits into a much longer history of racialized immigration and labour policies in Canada. Therefore, though we need to understand the changes wrought by neo-liberalism, we must also acknowledge the historical continuities inherent in SAWP: no matter who was in office, and what political ideology they subscribed to, migrant labour schemes have consistently been relied onto support the state's project of aiding the accumulation of wealth and filling the labour vacuum left behind by Canadians who gained safer, more secure, and more lucrative employment elsewhere.
Keywords: Social sciences

« Le jour du Seigneur vendu à l'encan » : regard sur la Commission d'enquête sur l'observance du dimanche dans les industries de pâtes et papiers du Québec (1964-1966) - Guillette, Bruno-Pierre (Université du Québec à Montréal, 2012)
Le Lord's Day Act interdit le travail le dimanche en 1906, mais autorise les travaux jugés nécessaires. Les compagnies papetières québécoises peuvent effectuer les travaux d'entretien et de nettoyage, mais ne peuvent pas produire le dimanche. L' industrie papetière exige la production continue et menace de freiner ses investissements au Québec si le gouvernement ne permet pas le fonctionnement des machines le dimanche. Le gouvernement Lesage instaure donc la Commission d'enquête sur l'observance du dimanche dans les usines de pâtes et papiers en 1964. Le jour du Seigneur fut essentiellement traité comme une question religieuse par les historiens, mais l'attachement pour la conservation du repos dominical déborde les questionnements sur le sécularisme ou la piété populaire. Cette commission instaurée pour régler un problème technique cache un profond conflit de valeurs entre les différents acteurs sociaux. Différentes façons de concevoir le bien commun et le progrès social y sont avancées. Aux séances de la commission, plusieurs groupes et individus font valoir leurs points de vue. Les représentants des compagnies papetières exigent unanimement la production le dimanche pour accroître la production. Pour les groupes religieux, la sanctification du dimanche est une manifestation collective vitale pour la cohésion de la famille, de la paroisse et de la société. Quant à eux, les travailleurs et leurs syndicats défendent l' idée d' un repos commun hebdomadaire et dénoncent le travail par rotation d'équipes. Les débats lors de la Commission Alleyn permettent de mettre en relief une confrontation culturelle à l' intérieur d'un rapport économique de production, tout en offrant un éclairage sur le bouleversement des nouveaux rapports sociaux en plein coeur de la Révolution tranquille.
Keywords: Alleyn, Commission d'enquête, Culture populaire, Dimanche, Temps de travail, Industrie papetière, Église, Religion, Repos dominical, Syndicat, Québec, Histoire.

Is Leisure Working? The State and the Gendered Regulation of Working Time and Leisure in Canada, 1950-2006 - Ignagni, Sandra (York University, 2012)
This dissertation examines the intersection of gender, employment law and public health policies through an analysis of the federal government's efforts to regulate the work/leisure relationship. The study asks how and why, despite over 50 years of state interventions to regulate leisure and healthy lifestyle, concerns about 'work-life balance' have surfaced in labour policy arenas in recent years. The study builds a feminist political economy framework for understanding changes in policy developments over time. I use the concepts of social reproduction and time- and work-discipline as lenses with which to probe the relationship between the changing temporal dimensions of paid and unpaid work and efforts to manage the new realities of the labour market through the institutions of the state. The dissertation considers how the changes in the gendered organization of social reproduction, the nature and regulation of employment, and the power of organized labour to advocate on behalf of workers have influenced the types of policies used to manage the work/life interface. The empirical dimension of this study traces the emergence of a framework for regulating social reproduction through state-led management of the work/life relationship. Following the evolution of such frameworks through federal policy debates, policy papers and program materials, I trace the continuities and changes in dominant leisure discourses and policy mechanisms through four phases of federal policy development: early fitness policies (pre-1960); ParticipACTION (1960 to early 1970s); employee fitness experiments (mid-1970s to 1990); and the Work/Life Balance Strategy (1990s to mid-2000s). The central argument put forward in this dissertation is that the gender- neutral and individualized framework for regulating the healthy reproduction of workers, developed in Canadian law and policy since the 1950s, has produced highly gendered outcomes through its failure to address the changing dynamics of work and family life. By continuing to uphold the notion of a worker 'unencumbered' by familial and household responsibilities, 'new' work-life balance policies exacerbate the tensions between paid and unpaid work and contribute to the ongoing marginalization of women in the labour market.
Keywords: Employment law; Gender; Leisure; Public health policies; Social sciences; Working

Pathways to Successful Economic Integration: The Dynamics of Low Income and Low Wages Among New Immigrants to Canada - Kaida, Risa Lisa (University of Toronto, 2012)
Contemporary research on immigrant economic integration identifies growing economic disadvantages faced by immigrants and probes sources of the disadvantages by focusing on immigrants' pre-migration and ascriptive characteristics. However, little empirical evaluation exists on how immigrants overcome their initial economic disadvantages over time. This dissertation departs from previous research by studying the roles of two post-migration factors - schooling (formal education and language training) and the employment of female spouses - in the exits from low wages and low family income (poverty) among recent immigrants. The analysis of the Longitudinal Survey of Immigrants to Canada (LSIC) - a three-wave survey of immigrants who arrived in Canada in 2000-2001 - produces three main findings. First, investing in host country formal education is beneficial for the economic advancement of new immigrants - especially highly educated ones. This finding confirms the role of skill upgrading programs for adult immigrants as an effective immigrant settlement policy, given that the majority of recent immigrants have postsecondary education but that their initial economic hardships are growing. Second, the benefits of English/French language lessons are real. This finding counters a common criticism that language lessons for adult new immigrants, which are often funded by the governments, are not helpful. Indeed, standard logistic regression analysis of the LSIC data shows that immigrants who enrolled in language lessons have no advantage in exiting poverty or low wages. However, the bivariate probit model demonstrates that this is because unmeasured characteristics of the language lesson participants confound the true benefit of language lessons. Third, this dissertation research highlights the role immigrant women play in lifting their families out of poverty when they work. This finding has an implication particularly for women of Arab and Middle Eastern origins as their notably lower labour force participation rates explain much of their high poverty rates.
Keywords: Demography; Economic integration; Ethnic and racial studies; Formal education; General; Immigrants; Language training; Low-income; Social sciences; Sociology; Spousal employment; Wages

L'Arsenal canadien: Les politiques canadiennes et la fabrication de munitions au Canada durant la Deuxième Guerre mondiale - Labbé, Pierrick (Université d'Ottawa, 2012)
Cette thèse propose une analyse de la production de munitions au Canada durant la Deuxième Guerre mondiale dans le but d'exposer les politiques mises de l'avant par le gouvernement canadien pour répondre aux exigences matérielles de la guerre. Afin de combler les besoins du ministère de la Défense et de ses alliés, le ministère des Munitions et Approvisionnements réussit un tour de force en transformant une industrie munitionnaire insignifiante en un vaste programme qui employait plus de 103 000 personnes à son apogée. L'analyse des politiques à l'origine de cette production montre que le gouvernement fédéral géra autant que possible sa contribution matérielle de manière à fournir une aide considérable à ses alliés tout en poursuivant ses objectifs de relance économique à long terme. Le Comité de guerre du Cabinet tenta également de limiter l'impact négatif de ses décisions sur la vie des Canadiens. La participation matérielle du Canada prit forme graduellement, restreinte par la volonté de limiter les dépenses militaires. Les projectiles ne figuraient pas parmi les priorités avant la chute de la France. À partir de l'automne 1940, les principaux ministères se montrèrent plus ouverts à la mise en place et au financement d'un vaste programme. Ils consolidèrent leur collaboration avec les gouvernements britannique et américain afin d'obtenir le soutien technique et financier nécessaire pour surpasser les faiblesses industrielles du pays, de manière à permettre une collaboration qui ne nuirait pas à long terme aux finances publiques. Ensuite, l'interventionnisme sans précédent pour stimuler ce secteur non traditionnel s'effectua, malgré l'ampleur des investissements, dans un esprit d'économie et mené par une volonté de ne pas disloquer inutilement les structures de l'économie civile. Le gouvernement misa sur une collaboration avec les entreprises compétentes qui dominaient déjà le marché. Les entrepreneurs jouèrent un rôle clé dans la stratégie fédérale de gestion des ressources humaines. L'élaboration d'une solution à la pénurie de travailleurs s'effectua autant que possible sans l'imposition de mesures coercitives, de manière à ne pas nuire à la relance de l'économie dans l'après-guerre et à ne pas saper le moral des citoyens. Le ministère des Munitions et Approvisionnements opta plutôt pour la mise en place d'un État-providence de guerre et d'un paternalisme industriel. Le secteur privé, appuyé par diverses initiatives du gouvernement fédéral, se devait d'imposer un encadrement strict du milieu de travail afin de maximiser la productivité, de diminuer l'absentéisme et de lutter contre les interruptions de production.
Keywords: Histoire de la Deuxieme Guerre mondiale; Histoire politique canadienne; Munitions; Social sciences; World War II

Topics in Canadian Aboriginal Earnings, Employment and Education: An Empirical Analysis - Lamb, Danielle Kathryn (University of Toronto, 2012)
This dissertation is divided into three main components that each relate to the socioeconomic wellbeing of Aboriginal peoples in the Canadian labour market. Specifically, using data from the master file of the Canadian census for the years 1996, 2001 and 2006, the first section examines the wage differential for various Aboriginal and non-Aboriginal groups, including a comparison of those living on-and-off-reserves. The study finds that, while a sizeable wage gap between Aboriginal and non-Aboriginal persons still exists, this disparity has narrowed over the three census periods for those living off-reserve. The Aboriginal-non-Aboriginal wage differential is largest among the on-reserve population and this gap has remained relatively constant over the three census periods considered in the study. The second study in the dissertation uses data from the master file of the Canadian Labour Force Survey for 2008 and 2009 to estimate the probability that an individual is a labour force participant, and, conditional on labour force participation, the probability that a respondent is unemployed, comparing several Aboriginal and non-Aboriginal groups. The results reveal that Aboriginal men and women have lower rates of labour force participation and higher rates or unemployment in both periods as compared to their non-Aboriginal counterparts. Aboriginal peoples were also disproportionately burdened by a slowdown in economic activity as measured by a change in the probability of unemployment moving from 2008 to 2009, as compared to non-Aboriginal people, who experienced a smaller increase in the probability of unemployment moving from a period of positive to negative economic growth. Finally, the third study examines the probability of high school dropout comparing Aboriginal peoples living on-and-off-reserve using data from the master file of the Aboriginal Peoples Survey for 2001. The findings reveal dramatically higher rates of dropout among Aboriginal people living on-reserve as compared to those living off-reserve. Limitations of all three studies as well as some possible directions of future research related to similar issues concerning Canada's Aboriginal population are discussed in the concluding chapter of the dissertation.
Keywords: Aboriginal peoples; Earnings; Education; Employment; Labor force activity; Social sciences; Unemployment

Labour Landmarks in Industrial Cape Breton, 1922-2011 - MacKinnon, Lachlan (University of New Brunswick, 2012)
Labour landmarks are memorial sites, commemorations, plaques, and burial sites that provide access to the themes and meanings of workers' past experiences. They are instrumental in enshrining workers' "public memories," which are the separate experiences of groups within society, within the larger "collective memory" of the community. A general exploration of the commemorative landscape reveals a number of themes and allows a detailed discussion of several labour landmarks. In the course of this research, 21 separate labour landmarks were identified in the communities of industrial Cape Breton. The majority of these monuments are dedicated to workers in the coal and steel industries. The 1980s saw an expansion in the frequency of labour commemorations, which indicates increased attention to the experiences of workers in Cape Breton. Two monuments in the community of New Waterford reveal the many layers of historical memory in the town. The first is dedicated to victims of the 1917 mine explosion, while the second commemorates the man killed during the 1925 strike. The explosion monument, unveiled in 1922, inserts the public memory of coal miners into the collective memory of New Waterford. The William Davis monument, dedicated in 1985, reveals an existing working-class consciousness in the town and merges individual and public memories of Davis while reflecting on a major event in the town's history. Another monument, dedicated to Sydney's steelworkers, now rests on the site of the former steel plant, and commemorates a century of experience. This memorial is used as an example of how one might "read" a labour landmark to access its themes and meanings, as well as to reach an understanding of the past experiences of workers.
Keywords: Social sciences

Rights of Temporary Foreign Workers in Canada - Macovei, Lidia (University of Alberta, 2012)
During the last decade, Canada experienced unequal economic growth. As result, the Canadian government expanded its Temporary Foreign Worker Program, which led to an essential change of its purpose, making it easier for employers to recruit temporary foreign workers for low-skilled jobs. In practice, TFWs are quite vulnerable without access to the same rights and privileges as Canadian citizens or permanent residents. The purpose of this thesis is to analyze whether the Canadian government respects the rights of TFWs through its domestic regulations and if such laws protect the rights of TFWs in practice. The thesis goal is to determine if the economic interest of the Canadian government and employers can be matched with international migrant rights' standards. It investigates international standards related to the protection of human rights, including covenants, international treaties, and human rights committees. This thesis also discusses similar programs governing TFWs in America, Germany, and Australia.
Keywords: Social sciences

Women in the Margins: Media Representations of Women's Labour in the Canadian Press, 1939-1945 - Moniz, Tracy (Ryerson University, 2012)
During the Second World War, women's participation in Canada's 'total war' effort meant increased domestic responsibilities, volunteering, enlisting in the armed forces, and joining the civilian workforce. Women's labour force participation more than doubled throughout the war, with more women working alongside and in place of men than ever before. This created a situation that could challenge the traditional sexual division of labour, and so women's labour became a subject for discussion in the public sphere. Through a comparative content analysis of the commercial and alternative (labour) press, this study examines representations of women's labour in wartime in the context of women's mobilization into the war effort through to subsequent demobilization near war's end. It first considers the theoretical and methodological issues involved in the historical study of news media and women and then offers original empirical research to demonstrate that when women's labour did emerge as a subject in the Canadian press, gender, not labour, was prioritized in the news. This was symbolically and systematically leveraged both within and across the commercial and alternative press, which reinforces stereotypical values about women and their labour and upheld the patriarchal status quo. In the end, while there were surface-level changes to the nature of women's paid labour during the war, the structures of female subordination and exploitation remained unchallenged despite women's massive mobilization into the workforce. By setting media representations against the wartime realities of women's labour told through archival records and secondary literature, this dissertation argues that news media generally presented a 'history ' of women's labour that did not reflect the lived reality or the political economic and social significance of women's labouring lives. This not only coloured how women's labour was represented in the news, but it can also shape the history that scholars construct from the newspaper. In contributing to feminist media and media history scholarship, this dissertation offers empirical evidence that challenges dominant ways of thinking about women's history in terms of the domestic sphere and furthers an understanding of women's wage labour as a provocation to such historical public-private divisions. This may, in turn, inspire histories that more fully and equitably capture women's experiences.
Keywords: Communication and the arts; Employment; Gender identity in mass media; Labor force; Media representations; Mobilization; Press; Social sciences; WORLD War, 1939-1945; Women workers; World War II

Race, Resistance and Co-Optation in the Canadian Labour Movement: Effecting an Equity Agenda like Race Matters - Nangwaya, Ajamu (University of Toronto, Ontario Institute for Studies in Education, 2012)
[Analyzes] the dialectic of co-optation/domestication and resistance as manifested in the experience of racialized Canadian trade unionists. The seven research participants are racialized rank-and-file members, elected or appointed leaders, retired trade unionists, as well as staff of trade unions and other labour organizations. In spite of the struggle of racialized peoples for racial justice or firm anti-racism policies and programmes in their labour unions, there is a dearth of research on the racialized trade union members against racism, the actual condition under which they struggle, the particular ways that union institutional structures domesticate these struggles, and/or the countervailing actions by racialized members to realize anti-racist organizational goals. While the overt and vulgar forms of racism is no longer the dominant mode of expression in today’s labour movement, its systemic and institutional presence is just as debilitating for racial trade union members. This research has uncovered the manner in which the electoral process and machinery, elected and appointed political positions, staff jobs and formal constituency groups, and affirmative action or equity representational structures in labour unions and other labour organizations are used as sites of domestication or co-optation of some racialized trade unionists by the White-led labour bureaucratic structures and the forces in defense of whiteness. However, racialized trade union members also participate in struggles to resist racist domination. Among some of tools used to advance anti-racism are the creation of support networks, transgressive challenges to the entrenched leadership through elections, formation of constituency advocacy outside of the structure of the union and discrete forms of resistance. The participants in the research shared their stories of the way that race and gender condition the experiences of racialized women in the labour movement. The racialized interviewees were critical of the inadequacy of labour education programmes in dealing effectively with racism and offer solutions to make them relevant to the racial justice agenda. This study of race, resistance and co-optation in the labour movement has made contributions to the fields of critical race theory, labour and critical race feminism and labour studies.

A Coal Miner's Shadow - Pelissero, Adam (Dalhousie University, 2012)
Light and shadow have the capacity to move us emotionally and create atmospheres that allow us to better understand stories. This thesis explores how light and shadow can propel the design of a music hall and museum space to commemorate the miners that lived and worked in the former industrial landscapes of Cape Breton, Nova Scotia, Canada.

Hurrah Revolutionaries and Polish Patriots: The Polish Communist Movement in Canada, 1918-1950 - Polec, Patryk (University of Ottawa, 2012)
This thesis constitutes the first full-length study of Polish Communists in Canada, a group that provided a substantial segment of the countries [sic] socialist left in the early 20th century. It traces the roots of socialist support in Poland, its transplantation to Canada, the challenges it faced within an ethnic community heavily influenced by Catholicism, the complications caused by its links to the Comintern, and its changing strength and decline. It offers a deeper understanding of the ways in which the Communist party was able to appeal to certain ethnic groups, such as through cultural outreach, as well as its complicated and often arguably counter-productive relationship with the Comintern. It also furnishes important information on the efforts of the RCMP and Polish consulates to maintain control over the communists, as well as how generally improved material conditions among Poles, especially following the Second World War, along with the influence of the Cold War, accounted for a rapid decline in support. The thesis is primarily based on sources generated by the Polish Ministry of Foreign Affairs or, more precisely, by the Polish consulates in Winnipeg, Montreal and Ottawa. One the Canadian side, the thesis took advantage of RCMP records, Canadian security bulletins, immigration records and Polish-language newspapers printed in Canada. By utilizing these sources, this study not only analyses the interaction of the Polish Canadian communist movement with other segments of the Polish community in Canada, but it also moves beyond the introverted approach that has characterized most studies of ethnic organizations in Canada by placing the movement within a "Canadian" context to analyze its relations with the government, broader segments of Canadian society, and the Communist Party of Canada (CPC).
Keywords: Albert; Communist Party of Canada; Dutkiewicz; Ethnic Polish; Glos Pracy; Immigration; Kronika Tygodniowa; Labor radicalism; Morski; Polonia; Polskie Towarzystwo Ludowe; Royal Canadian Mounted Police (RCMP); Social sciences; Wladyslaw

How the Media View Public-Sector Workers: A Critical Discourse Analysis of a 2009 Municipal Workers' Strike in Windsor, Ontario - Reitsma, Travis G. (University of Windsor, 2012)
Research in the field of media coverage of organized labour has found that there often exist biases in the way in which unions and their workers are presented. With the ever increasing influence of both the media and neoliberal political and economic ideologies, the public image of organized labour has come under attack. This thesis seeks to expose another instance of this bias in the Windsor Star 's coverage of a 2009 municipal workers' strike in Windsor, Ontario, Canada; a public-sector strike. A detailed critical discourse analysis (CDA) was conducted on 480 texts regarding the strike in 2009. An anti-union bias was found especially throughout the coverage. This bias can be seen to have a detrimental effect on the image of public-sector workers which serves to further discredit them in their struggle against neoliberal power structures which seek to minimize their influence.
Keywords: Communication and the arts; Critical discourse analysis; Labor strikes; News bias; News coverage; Social sciences

Labour Force Participation and Health-related Quality of Life in People Living with HIV - Rueda, Sergio Ismael (University of Toronto, 2012)
This dissertation consists of four papers aimed at understanding the complex relationship between employment and health. One paper is a systematic review of the return to work literature, while the other three papers used secondary data from three cohorts of people with HIV to examine the association between employment and health-related quality of life. The systematic review looked at longitudinal studies that reported health outcomes associated with return to work in relation to other employment trajectories. This review supported the beneficial effect of return to work on health in a variety of populations, times, and settings, and also found evidence that poor health interferes with the prospects of returning to work. Two other papers looked at the association between employment and health-related quality of life in people with HIV; one paper used a cross-sectional sample of people with HIV, while the other paper used a longitudinal sample of men who have sex with men. These two studies found evidence to support the association between employment and both physical and mental health-related quality of life. They also found that employment had a stronger relationship with physical than mental health, suggesting an adaptation process to the experience of unemployment. Finally, another paper examined the cross-sectional association between job security and quality of life in men and women living with HIV. This study found that job security offered additional mental health quality of life benefits, over and above participation in employment alone, for men living with HIV. On the other hand, women benefited from the availability of work, but the perception of job security failed to offer additional health benefits. The current level of evidence on the relationship between work and health in HIV needs to be strengthened by further research to develop and support practical clinical and policy recommendations.

Solidarity Forever, Canadians Never: SAWP Workers in Canada - Russo, Robert Marc (University of British Columbia, 2012)
This doctoral thesis focuses on collective bargaining and temporary migrant workers within Canada participating in the Seasonal Agricultural Workers Program (SAWP). The intent is to analyze the range and efficacy of legal responses to the problems encountered by this community within Canada, focusing on the unionization of SAWP participants. The dissertation addresses the fundamentally legal relationship between unionization and SAWP workers in Canada. It takes an approach that considers both historical and legal considerations leading to the use of SAWP workers in Canada, and the eventual attempts at unionization. Recent legal developments in several Canadian provinces involving SAWP workers and efforts collective bargaining are analyzed. There is a comparison with similar efforts to unionize migrant workers in the United States, and of efforts to address violations of collective bargaining rights through international complaints as well as within the broader framework of international law. The conclusion reached is that within the current framework of provincial labour legislation and the current structure of the SAWP, collective bargaining alone represents an inadequate response to violations of SAWP workers’ workplace rights in Canada.
Keywords: Seasonal Agricultural Workers Program (SAWP)

No Quarter Required: Japanese Experiences and Media Distortions in the Steveston Fishers’ Strike of 1900 - Stielow, Timothy Mark (Simon Fraser University, 2012)
The brief histories of the Steveston Fishers’ Strike of 1900 are dominated by the arrival of the militia on 24 July and images of racialized violence between Japanese and white fishers. This thesis analyzes Japanese language sources and re-evaluates contemporary English language press reports to expand the strike narrative and demonstrate that Japanese fishers held significant negotiating power throughout the standoff. It argues that labeling Japanese as strikebreakers ignores their perspectives and goals in the labour dispute; however, this thesis also explains that there were important differences within the Japanese community and that to speak of a single Japanese perspective is to privilege individuals in positions of power who benefitted financially from fellow community members. It also demonstrates that by emphasizing tensions between groups of fishers, existing histories overlook the fact that the most violent acts of the month were done by the cannery owners through their connections with government.

The Social Organization of the Ontario Minimum Wage Campaign - Wilmot, Sheila (University of Toronto, Ontario Institute for Studies in Education, 2012)
My dissertation research is interdisciplinary in nature, at the nexus of three areas of scholarly work and actual practices: union renewal and non-unionized workers-rights organizing in Canada and the US; feminist, anti-racist Marxian approaches to class relations as being racialized, gendered and bureaucratic; and, the institutional ethnographic method of inquiry into social reality. My empirical focus is on the Ontario Minimum Wage Campaign (OMWC). The OMWC was a Toronto-based labour-community project to raise the minimum wage to $10 per hour. It was started in 2001 by Justice for Workers (J4W), was carried on by the Ontario Needs a Raise coalition (ONR) from 2003 to 2006, and was re-launched in 2007 by the Toronto and York Region Labour Council (TYRLC) in association with some community groups. The OMWC brought together across time and space activist groups, community agencies and labour organizations, all of whose volunteers, members, clients, educators, officials and staff were the agents and/or targets of the campaign. The apparent victory of the OMWC is quite contested. Local campaign realities were compartmentalized in numerous ways and OMWC involvement met different institutionally specific and coordinated needs. And while coalitions generally arise as vehicles to transcend such institutional separation, the campaign was challenged to materially bridge such compartmentalization. The fragmentation of reality amongst institutions and how it was managed in practice affected how collaboration, participation, and decision-making happened and appeared to have happened in organizing and educational activities. While there were at times transformative intentions, there was generally a pragmatic anti-racist organizing practice and effect. I contend that the complexity of contemporary society poses great challenges for the possibilities for human-agency based labour-community workers-rights organizing with a broad-based, political capacity for movement building orientation. I suggest that this is largely so because the social coordination of what we do and what we understand about what we do turns on at least three components of social reality: an institution-based organization of multi-layered social relations that is generally locally circumscribed but extralocally driven; a conditioned individually-driven orientation to meeting human needs; and an ideological orientation to both the content of ideas and thought, and the process of that reasoning.

National Holidays and Minority Festivals in Canadian Nation-Building - Zhu, Lianbi (University of Sheffield, 2012)
This study of Canadian national holidays examines their role as a complex and dynamic instrument of nation-building from 1867 to the early 2000s. It indentifies three phases of nation-building, labelled assimilation, transformation and multiculturalism. It takes the ideological change in Canada in 1971, namely the proclamation of Official Multiculturalism, as the momentous turning point which motivated the pioneering changes and creation of Canadian national holidays based on negotiations in the government and the interventions of varied ethnic groups, focusing on the relationship between the commemorative and recreational functions of these holidays. Specific holidays considered including Dominion Day (Canada Day), Labour Day, Victoria Day and Remembrance Day, as well as National Aboriginal Day, Canadian Multiculturalism Day and one minority festival – Chinese New Year. Counterparts in France and the United Kingdom are presented to contrast with Canadian practices, putting Canada in the global context of nation-building and decolonisation. It argues that debates surrounding national holidays are a good measure of underlying national ideology, which underwent a real change in Canada across the period studied.